Langbourne - Landau, Alan P.; Landau, Alan P. ([Rothwell, Queensland] : [Alan P. Landau], 2014)
Set in 1891, Langbourne tells the story of two young Polish Jewish brothers who set sail for Africa from Ireland to seek a better life. Morris and David arrive in Port Elizabeth, South Africa, and quickly put their business plan into action. Based on a true story and actual events.
Ages 13+.
Keywords: Brothers -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Jews -- South Africa -- Juvenile fiction; South Africa -- History -- 1836-1909 -- Juvenile fiction; Australian; Historical fiction; Young adult fiction